METODE SINKRONISASI INVERTER SATU FASE DENGAN JARINGAN LISTRIK YANG TERDISTORSI - Bambang Sujanarko (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
DC power sources from renewable energy sources that would be connected to the electricity grid system require synchronization process. This process is implemented by controlling the inverter in a way to obtain instantaneous amplitude, phase and frequency according to the electricity network. This research discussed a method for synchronizing VSI PWM inverters connected with distorted single-phase power grid using a filter as a pure sine generator, and a compensator as the restorer of angle change due to the power filtering. Results of simulation using MATLAB show that this method can produce better synchronization compared to other synchronization methods, as it successfully produce similar phase and waveform with the grid’s waveform.